Parkinson's Disease : Non-Motor and Non-Dopaminergic Features - Olanow, C. Warren; Stocchi, Fabrizio; Lang, Anthony E. (Wiley-Blackwell, 2011)
Parkinson's Disease has traditionally been seen as a movement disorder, and diagnosed by the development of tremor. However, we are beginning to understand that the disease manifests itself in many ways, and that earlier diagnosis might be possible through non-tremor symptoms. This textbook aims to tell the full story of non-motor and non-dopaminergic features of Parkinson's Disease.
Includes bibliographical references and index.
Keywords: Parkinson's disease -- Diagnosis; Parkinson's disease -- Pathophysiology; HEALTH & FITNESS -- Diseases -- Alzheimer's & Dementia; MEDICAL -- Neurology; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Electronic resource; Electronic books